2012
DOI: 10.1186/1742-2094-9-138
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal apoptosis by HIV-1 Vpr: contribution of proinflammatory molecular networks from infected target cells

Abstract: BackgroundHuman immunodeficiency virus type 1 (HIV-1) induces neuronal dysfunction through host cellular factors and viral proteins including viral protein R (Vpr) released from infected macrophages/microglia. Vpr is important for infection of terminally differentiated cells such as macrophages. The objective of this study was to assess the effect of Vpr in the context of infectious virus particles on neuronal death through proinflammatory cytokines released from macrophages.MethodsMonocyte-derived macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 65 publications
4
60
0
Order By: Relevance
“…Here, we infected CD4 ϩ T cells with wildtype or vpr-deleted viruses and observed that Vpr stimulates the secretion of TNF in productively infected cells. Our results confirm and extend earlier studies showing that CD4 ϩ T lymphocytes, dendritic cells, and macrophages infected by HIV produce higher levels of TNF in the presence of Vpr (79,81,82). Using inhibitors of reverse transcription and integration, as well as ⌬vpr viruses complemented in trans with HA-Vpr, we found that de novo synthesis of Vpr was required for this effect.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Here, we infected CD4 ϩ T cells with wildtype or vpr-deleted viruses and observed that Vpr stimulates the secretion of TNF in productively infected cells. Our results confirm and extend earlier studies showing that CD4 ϩ T lymphocytes, dendritic cells, and macrophages infected by HIV produce higher levels of TNF in the presence of Vpr (79,81,82). Using inhibitors of reverse transcription and integration, as well as ⌬vpr viruses complemented in trans with HA-Vpr, we found that de novo synthesis of Vpr was required for this effect.…”
Section: Discussionsupporting
confidence: 81%
“…Vpr has been reported to inhibit the secretion of type I interferon (IFN) (33,62,72,73) and of other proinflammatory cytokines such as tumor necrosis factor (TNF), MIP-1␣, MIP-1␤, and RANTES (74,75). In contrast, other studies suggested that Vpr stimulates type I IFN production in astrocytes (76) and induces interferon-stimulated genes (ISGs) in macrophages and monocytes (77,78) and the proinflammatory cytokines interleukin-1␤ (IL-1␤), IL-8, and TNF in various cells (70,71,(79)(80)(81)(82). These opposing results may reflect cell type differences or the use of different methods to express Vpr (infection, overexpression of Vpr, and treatment with Vpr recombinant protein).…”
mentioning
confidence: 52%
“…Vpr alone induces the production of pro-inflammatory cytokines, such as IL-6, IL-8, MCP-1, and CCL5, from astrocytes and macrophages [169, 181, 182]. Induction of cytokines involves the activation of p38 MAPK, JNK MAPK, TLR4/MyD88, and NF-0κB signaling pathways [169, 183]. Infusion of Vpr-transfected astrocytes into the hippocampus impairs spatial and recognition memory in rats and induces morphological changes in neurons with reduced expression of synaptophysin [184].…”
Section: Role Of Hiv-1 Proteins In Neurotoxicitymentioning
confidence: 99%
“…Although HIV-1 does not replicate in neurons, its productive infection in other cell types leads to the release of neurotoxic viral proteins, such as Tat, Nef, Vpr and gp120 [30,31,32,33]. These viral proteins induce neuronal apoptosis and affect axonal projections to their targets, impairing neuronal plasticity and function [34,35,36,37,38,39,40,41]. Moreover, the chronic immune activation due to HIV-1 proteins and other antigens (as discussed below) results in a persistent proinflammatory condition in the CNS with concomitant homing of anti-HIV-1-specific CD8+ T lymphocytes to this site, which may accentuate the cell death [42].…”
Section: Hiv-1 Infectionmentioning
confidence: 99%
“…The HIV-1 proteins Tat, Nef, gp120 and Vpr can cause neuronal loss, either due to proapoptotic stimuli or by impairing axonal projections and neuronal plasticity/function, especially in sympathetic neurons [34,35,36,37,38,39,40,41]. NT signaling through Trk receptors has been associated with anti-apoptotic activity and with enhancement of synaptic connections, and many works, using different cellular models and treatment strategies, have shown that NGF and BDNF are able to recover neuronal plasticity impaired by HIV-1 proteins and to rescue neuronal cells from HIV-1-induced apoptosis [119,120,121,122].…”
Section: Ngf Other Nts and Hiv-1 Infectionmentioning
confidence: 99%